2010
DOI: 10.1016/j.psychsport.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic and psychological effects of synchronous music during circuit-type exercise

Abstract: ObjectivesMotivational music when synchronized with movement has been found to improve performance in anaerobic and aerobic endurance tasks, although gender differences pertaining to the potential benefits of such music have seldom been investigated. The present study addresses the psychological and ergogenic effects of synchronous music during circuit-type exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 26 publications
6
66
3
6
Order By: Relevance
“…The present findings are concordant with recent findings relating to the effects of motivational and neutral music on anaerobic tasks (e.g., Karageorghis et al, 2010;Terry et al, 2012) albeit that these recent findings pertain to the synchronous application of music.…”
Section: Practical Implications Of the Present Findingssupporting
confidence: 92%
See 3 more Smart Citations
“…The present findings are concordant with recent findings relating to the effects of motivational and neutral music on anaerobic tasks (e.g., Karageorghis et al, 2010;Terry et al, 2012) albeit that these recent findings pertain to the synchronous application of music.…”
Section: Practical Implications Of the Present Findingssupporting
confidence: 92%
“…There was high variability in the state attention scores (see Table 2), which prevented the interaction effect from emerging as significant (p > .05). Previous studies have shown that females can derive greater benefit from music than males in affective terms (e.g., Karageorghis et al, 2010), but the present finding pertaining to attentional focus warrants further investigation.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Contrastingly, when music is used asynchronously, it provides background stimulation without conscious synchronisation between movement patterns and musical tempo 1 . Music has been shown previously to provide ergogenic (i.e., increased work output), psychological (e.g., enhanced emotional responses), psychophysical (i.e., reduced perceived exertion) and psychophysiological (e.g., improved oxygen consumption) effects in sport and exercise contexts [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%